Congenital muscular dystrophies: classification and diagnostic strategy - François Rivier; Pierre Meyer; Ulrike Walther-Louvie; Moïse Mercier; Bernard Echenne; Susana Quijano-Roy (Нервно-мышечные болезни, 2015)
Congenital muscular dystrophies (CMD) are a large group of genetically determined muscular diseases, initially defined by an early onset before the age of walking and dystrophic changes on myopathologic analyses. Currently, their definition is less restrictive with, a clinical continuum with limb-girdle muscular dystrophies, and closer histomorphological aspects with congenital myopathies. We distinguish 9 different forms of DMC, classified in 6 different groups depending on the location and/or function of the protein involved, on the control of 26 different genes. Ullrich's disease, UCMD (collagenopathy involving three different genes: COL6A1, COL6A2, COL6A3); secondary dystroglycanopathies (by abnormal glycosylation of alpha-dystroglycan involving 16 different genes); and DMC merosin negative, MDC1A, (merosinopathy secondary to mutations in a unique gene, LAMA2); represent the three most common forms. Rigid spine syndrome type 1, RSMD1 (selenopathy secondary to SEPN1 gene mutation) and L-CMD (laminopathy involving LMNA gene) are also part of the most current forms. Clinical features, plasmatic creatine kinase elevation or not, the presence or absence of clinical signs of central nervous system involvement, allow a first level of diagnostic pathway. According to these elements, muscle and/or cerebral MRI, muscle and/or skin biopsy will be discussed to guide the molecular investigations that will allow accurate diagnosis.